Owen Jones. The Establishment. And How They Get Away With It. London, Penguin Books, 2014, 358 págs., ISBN: 978-1-846-14719-7. - Largo Jiménez, Fernando (Investigaciones de Historia Económica, 2019)
Sin resumen